Frankfurt am Main, Deutschland. ClaReNet. Klassifikation und Repräsentation keltischer Münzprägungen im Netz. Das Projekt von 2021 bis 2024 - Wigg-Wolf, David; Hofmann, Kerstin P.; Tolle, Karsten; Rösler, Katja; Möller, Markus; Deligio, Chrisowalandis; Tietz, Julia; von Nicolai, Caroline (e-Forschungsberichte des DAI, 2022)
The joint project ClaReNet, funded by the Federal Ministry of Education and Research, is testing the possibilities and the limits of new methods of classification and representation on the basis of three Celtic coinages, each selected as an example for specific research questions and problems. Traditional approaches to classification in numismatics and archaeology are compared with classification methods from information technology, including deep learning. An extendable virtual union catalogue, celticcoinage.org, complying with the FAIR principles, will be implemented for the coin series that we are investigating. The work process will be accompanied by a science and technology study, which will contribute to a reflection on the changes in knowledge processes that result from the use of digital tools and algorithms. The aim is to systematically assess in an interdisciplinary dialogue the potential and limits of automation for processes of classification and representation in numismatics and archaeology.